El estudio contrastivo-pragmático entre primeras y segundas lenguas de los registros formal y coloquial - Fernández Jódar, Raúl (Studia Romanica Posnaniensia, 2021)
In this article we intend to present the theoretical bases for the contrastive study of colloquial and formal registers from a pragmatic point of view. Although we start from the point of view of contrastive linguistics, we consider that neither the comparison of the theoretical grammars of two languages, nor the description of specific actions of learners of an L2, can show the nuances of the formal and colloquial registers. Formal and colloquial registers should not be understood as watertight departments with no relationship between them, but as two extremes within the continuum of speech. Obviously, this continuum will differ depending on the language in question, since certain lexical, pragmatic or syntactic elements, among others, can be understood as corresponding to different registers. Now, how should we face the contrast of this continuum belonging to different languages? In the paper we present both the techniques used to measure the attitude of the interviewees regarding different elements of the colloquial and formal records, as well as the concepts that will help us to analyse the data obtained. Finally, the analysis can draw conclusions that refer to the learning process and the teaching process.